PERCEPATAN PEMIJAHAN LELE DENGAN INDUKSI LASERPUNKTUR UNTUK MEMPRODUKSI BENIH SKALA MASSAL - Dyah Hariani; Pungky Slamet Wisnu Kusuma (JPM17: Jurnal Pengabdian Masyarakat, 2017)
The seedling unit of  Mulyorejo  is  one  breeder  catfish  has  implemented  the way of a good and true fish hatchery  system and  quality  of  seeds produced and certified so that many invaded by consumers of catfish enlargement  group. But the problem  is  that  the  UPR  has  not  been  able  to  needs  of  consumers  seed. UPR  is  targeting production of 12 million of seeds during the rainy season, but in reality only able to supply seeds of catfish in the market about 5 million fries so that there is a shortage of 7 million fries. Therefore, it  is  necessary  that  the  appropriate   technology  breakthroughs  Laserpuncture  technology  to accelerate  the provision of gonads mature  broodstock catfish and catfish seed supplies in bulk and  continuously  to  support  the  success,  sustainability  and  development  of  catfish  farming through  socialization.  The  method  is  applied  to  training  programs  for  the  dissemination  of technology laserpuncture as an  effort to accelerate  the broodstock catfish  mature  gonads  and seed production a mass scale in the group breeder catfish "Mulyorejo" in the village of Maguan, followed by giving dempond, operating  practices laserpuncture and induction  laserpuncture in dot reproduction  appropriately  as  well as  assistance  to the  group  breeder    catfish  as  trained partners.  From the results of this socialization, some catfish breeder   has applied laserpuncture technologies   for   spawning   of   broodstock   catfish   and   eggs   were   overripe   oviposition simultaneously  and evenly desperate   in the spawning pond and seeds produced may reach  80-90%, which impacted positively with an increase in revenue.